The landscaping of Upper Silesia after 1989 - Kosterska, Alicja (Polskie Studia Krajobrazowe, 2019)
The paper offers a critical analysis of the representations of post-industrial landscapes in Upper Silesia. It takes a look at the products of visual culture after 1989: feature films set in the region and photographs by Wojciech Wilczyk, trying to detect their embedded ideological mechanism and explain its dynamics. Drawing on the concepts advanced by Tim Edensor and W.J.T. Mitchell, the paper demonstrates that that mechanism consists in using aestheticization tools and sight cropping, following which a comprehensive view is feigned. As a result, Upper Silesia appears to be a degenerate space affected by permanent stagnation. In closing, the requirements that representations of landscape should meet are enumerated in order to provide insights into the diversity of a region, as well as offering a point of departure for reflection on its place in the national imagination. Ultimately, these considerations enable the expression of Upper Silesian identity from a position other than that of inferiority and subordination.